Understanding intercultural communication negotiating a grammar of culture - Holliday, Adrian (London New York Routledge/Taylor & Francis Group, 2019)
"Understanding Intercultural Communication provides a practical framework to help readers to understand intercultural communication and to solve intercultural problems. Each chapter exemplifies the everyday intercultural through ethnographic narratives in which people make sense of each other in home, work and study locations. Underpinned by a grammar of culture developed by the author, this book addresses key issues in intercultural communication including: - the positive contribution of people from diverse cultural backgrounds; - the politics of Self and Other which promote negative stereotyping; - the basis for a de-centred approach to globalization in which periphery cultural realities can gain voice and ownership. Written by a leading researcher in the field, the new edition of this important text has been revised to invite the reader to reflect and develop their own intercultural and research strategies, and updated to include new ideas that have emerged in Holliday's own work and elsewhere. This book is a key resource for academics, students and practitioners in intercultural communication and related fields"-- Provided by publisher.
The grammar of culture -- Cultural practices -- Investigating culture -- Constructing culture -- Dialogue with structure -- Grand narratives of nation and history -- Discourses of culture -- Prejudice -- Cultural travel and innovation.
Prof. Belinda Espiritu (Recommending faculty) - Bookfair 2019
Includes bibliographical references (pages 182-190) and index.
Keywords: Intercultural communication